PENGARUH KINERJA BISNIS, ITENSITAS PENELITIAN DAN PENGEMBANGAN, DAN HUTANG PERMODALAN TERHADAP KINERJA KEUANGAN INDUSTRI TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2016-2020 - Lidwina Ratna Swastita Indraswari (2022)
This study aims to analyze the influence between the implementation of business diversification, CSR activities, product strategy on firm value in the Hospitality Industry in Indonesia in the period 2017-2020. This research methodology uses quantitative methods with a research sample of 38 companies listed on the IDX. The data analysis technique used is regression and regression with moderating. This research was processed using E-views and Microsoft Excel. The results showed that simultaneously the variables of Business Diversification (X1), CSR Activities (X2) and Product Strategy (X3) had a significant effect on firm value (Y). Meanwhile, the foreign ownership variable is not able to moderate the relationship between CSR activities and product strategy on firm value. Keywords: Financial Performance, Bisnis Performance, Research and Development Intensity (RDI), dan Financial Leverage